Sistema de Información Radiológica XAVIA RIS. - Vega Izaguirre, Leodan; Ciudad Ricardo, Febe Ángel; Duque García, Eddy Yanier; Soler Izquierdo, Geidar (Revista Cubana de Informática Médica)
The XAVIA PACS Medical Images Storage, Transmission and Visualization System, developed by the University of Computer Sciences is used in multiple Cuban health institutions. The purpose of these tools is to manage the medical image, so they do not manage the information that is captured in the diagnostic imaging services, among which are the patient's data, the imaging study and the diagnostic report. This article presents a computer system for the management of imaging information integrated into the XAVIA PACS system to ensure automated control of information in diagnostic imaging services. For the planned development, the need to reuse the source code already implemented in the XAVIA PACS system was decisive; Microsoft.NET Framework, ASP.NET 3.5, C # 3.5 were selected as the programming language, PostgreSQL as the Database management system. Additionally, portability, complex internal processing, ease of installation, and ease of change were considered. The developed system automates the management of work lists in diagnostic imaging services, the management of patient information, appointments, work planning of medical modalities, and radiology specialists. The implementation of the system developed in different health institutions that use the XAVIA PACS system, validated its relevance and applicability.